Peran Retrun On Assets (ROA) Sebagai Variabel Mediasi Pada Pengaruh Non Performing Loan (NPL) Dan BI Rate Terhadap Harga Saham Bank BUMN Periode 2011 – 2020 - Yayan Nasikin; Indah Yuliana (Politeknik Ganesha Medan, 2022)
The purpose of this study is to provide empirical evidence regarding the direct effect of Non Performing Leon (NPL) and BI Rate on Return On Assets (ROA) and stock prices, indirect effect of Non Performing Leon (NPL) and BI Rate on stock prices through Return On Assets (ROA) as a mediating variable in state-owned banks for the period 2011 – 2020. This type of research is quantitative research. The data analysis technique used is multiple linear regression and mediation test using Eviews 12 program and Sobel Test Online. The results of this study show that simultaneously Non Performing Loans (NPL), BI Rate and Return On Assets (ROA) have a significant effect on stock prices. Partially 1). Non-performing loans (NPL) have a negative and significant impact on Return On Assets (ROA). 2) BI Rate has a positive but not significant impact on Return On Assets (ROA). 3). NPL (Non Performing Loan) has a negative and significant impact on stock prices. 4). BI Rate has a negatif and significant impact on stock prices. 5) Return on Assets (ROA) has a positive and significant impact on stock prices. Return on Assets (ROA) as a mediating variable is able to mediate the effect of non-performing loans (NPL) on stock prices, however, Return On Assets (ROA) does not mediate the effect of the BI Rate on stock prices.